Furniture Bergaya Tradisional Indonesia pada Restoran Kampung Daun - Taufik Firdaus, Boyke Arief; ., Sakinat (FSRD ITENAS, 2011)
Abstract Use of furniture not just seen from side of function requirement or just its usefulness, but rather from that its also attend as one of space component which can become the atmosphere creation expected at the space. Furniture as one of space component, along with other space component designed become one union in the space utilize to reach the space atmosphere expected. Style represent one of determinant appliance in instructing every space component visually in reaching the space atmosphere, so that style union between space and furniture become one of measuring rod in determining according to form, colour, material and construction of every space component. That way the things of furniture design used at restaurant of Kampung Daun of Culture Gallery & CafÃ©. The atmosphere expected by attend at this restaurant is Indonesian traditionaly countrified atmosphere, what at one blow become the theme and style which have been determined by since the early concept its development. Hence furniture design which the using of even also shall owning same style, is so that expected can be created that atmosphere. The style of furniture which designed ought to the style of Indonesian traditionaly furniture where used in Indonesian countrified. Keyword: Indonesian Traditional Furniture style, Restaurant of Kampung Daun. Abstrak Penggunaan furnitur tidak hanya sekedar dilihat dari sisi kebutuhan akan fungsi atau kegunaannya saja, tetapi lebih dari itu ia juga hadir sebagai salah satu komponen ruang yang dapat menjadi bagian dalam terciptanya suasana yang diharapkan pada ruang tersebut. Furnitur sebagai salah satu komponen ruang, bersama dengan komponen ruang lainnya didesain menjadi satu kesatuan pada ruang tersebut guna mencapai suasana ruang yang diharapkannya. Gaya atau style merupakan salah satu alat penentu dalam mengarahkan setiap komponen ruang secara visual dalam mencapai suasana tersebut, sehingga kesatuan gaya antara ruang dan furniturnya menjadi salah satu tolok ukur dalam menentukan kesesuaian bentuk, warna, material dan konstruksi pada masing masing komponen ruangnya. Demikian halnya pada desain furnitur yang digunakan pada restoran Kampung Daun Culture Gallery & CafÃ©. Suasana yang diharapkan hadir pada restoran ini adalah suasana perkampungan tradisional Indonesia, yang sekaligus menjadi tema dan gaya yang telah ditentukan sejak konsep awal pembangunannya. Maka desain furnitur yang digunakanyapun haruslah yang memiliki gaya yang sama, sehingga diharapkan dapat tercipta suasana tersebut. Gaya furnitur yang didesainnya harusnya gaya furnitur tradisional Indonesia yang digunakan di perkampungan Indonesia. Kata kunci: Furniture Gaya Tradisional Indonesia, Restoran Kampung Daun.